Pelatihan Penyusunan Proposal Event Bagi Masyarakat Desa Panji, Buleleng - Wirata, I Nengah; Widaharthana , I Putu Esa; Suprastayasa, I Gusti Ngurah Agung; arjaya, ketut; Citrawati, Luh Putu; Ariasri, Nyoman Reni; Paramita , Ratri; Kusumarini, Indah; Sumadi, I Gede; Swandewi, Ni Kadek; Baskara, I Made Lingga (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Panji tourist village, Sukasada District, Buleleng has very unique and interesting natural and cultural tourism potential to be developed. Its development requires guidance, especially tourism awareness groups and local communities, on how to maximize this potential so that it can attract tourists and improve the welfare of local communities. Looking at the conditions and analysis of the needs of the local community, training in the form of knowledge and skills is needed in the field of developing the potential of the Panji tourist village through festival events. This activity was carried out through community service in stages by the Convention and Event Management Study Program, Bali Tourism Polytechnic with the aim of providing training in preparing event proposals for the Panji Buleleng Tourism Village community. Using a combination of theoretical lectures and hands-on practice, the training successfully produced five event proposals, including the